Effect of Standardized Ileal Digestible Lysine to Crude Protein Ratio on Growth Performance of 100 to 275 lb Pigs - Ron Aldwin S. Navales; Abigail K. Jenkins; Ty H. Kim; Julian Arroyave; Joel M. DeRouchey; Katelyn N. Gaffield; Jordan T. Gebhardt; Robert D. Goodband; Mike D. Tokach; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2025)
Four experiments were conducted to determine the effect of SID Lys to CP ratio (SID Lys:CP) on growth performance and blood urea nitrogen (BUN) of 100 to 275 lb pigs. In each experiment, pens of pig were blocked by BW and randomly assigned to one of five dietary treatments in a randomized complete block design. There were eight to 10 pigs per pen and 13 or 14 replications per treatment in each experiment. A total of 621, 663, 624, and 609 pigs were used in Exp. 1 through 4, respectively. The pigs were DNA 600 × 241 and had initial BW of 100.3 ± 1.17 lb, 121.5 ± 1.08 lb, 187.0 ± 1.88 lb, and 228.7 ± 1.34 lb for Exp. 1 to 4, respectively. Pens were mixed gender, and each experiment lasted 21 d. Dietary treatments were corn-soybean meal-based and formulated to contain 0.94, 0.83, 0.71, and 0.63% SID Lys for Exp. 1 to 4, respectively. Within each experiment, diets provided SID Lys:CP ratios of 85.0, 92.5, 100.0, 107.5, and 115.0% of requirement estimates calculated from NRC (2012). Intermediate SID Lys:CP levels were achieved by blending diets with the lowest and highest SID Lys:CP ratio. Pen weight, number of pigs per pen, and feed delivery were recorded to calculate ADG, ADFI, and F/G. Blood samples were collected on d 14 of each experiment and analyzed for BUN. Dose response curves were evaluated using linear, quadratic polynomial, cubic polynomial, and broken-line linear (BLL) models. In Exp. 1, increasing SID Lys:CP had no effect on final BW and ADG, but it increased (linear, P < 0.001) ADFI and worsened (linear, P < 0.001) F/G. In Exp. 2, increasing SID Lys:CP ratio did not influence final BW, but tended to decrease (linear, P = 0.053) ADG, increase (quadratic, P = 0.025) ADFI, and worsen (linear, P < 0.001) F/G. In Exp. 3, increasing SID Lys:CP ratio decreased (linear, P ≤ 0.046) final BW and ADG, and worsened (linear, P < 0.001) F/G. In Exp. 4, increasing SID Lys:CP had no influence on final BW and ADG, but tended to increase (linear, P = 0.069) ADFI and worsened (linear, P = 0.009) F/G. Across experiments, increasing SID Lys:CP decreased (linear, P ≤ 0.001) nitrogen (N) intake and BUN. The cubic models provided the best fit for Exp. 1, 2 and 4, while the linear model provided the best fit for Exp. 3. In conclusion, increasing SID Lys:CP worsened F/G and decreased BUN in 100 to 275 lb pigs. Based on the local minimum determined using the cubic models, the estimated SID Lys:CP ratios to optimize F/G for pigs weighing 100 to 153 lb, 121 to 172 lb, and 228 to 275 lb were 5.55%, 5.43%, and 5.23%, respectively. For pigs weighing 187 to 238 lb, the requirement was estimated to be below 5.13% based on the linear model. These SID Lys:CP ratios are below NRC (2012) estimates.
Keywords: crude protein; growing pigs; SID Lys; SID Lys:CP ratio